Addition of 2D Ti3C2Tx to Enhance Photocurrent in Diodes for High‐Efficiency Organic Solar Cells. Issue 4 (9th March 2021) - Zhao, Yong; Liu, Xiaojie; Jing, Xin; Wang, Xiangkun; Gao, Caiyun; Dai, Shuixing; Yu, Liangmin; Sun, Mingliang
Abstract : Solution‐processed 2D Ti3 C2 T x nanosheets are incorporated into the active layer of organic solar cells (OSCs) as a third component to obtain an enhancement of the photovoltaic device performance. The power conversion efficiency (PCE) of the devices is boosted from 9.34% to 10.72% for the PBDB‐T:ITIC blend and from 14.64% to 16.25% for the PM6:Y6 blend after adding 2D Ti3 C2 T x nanosheets. The light scattering of the 2D flakes in Ti3 C2 T x nanosheets not only increases the short‐circuit current density ( J SC ) but also improves the carrier dissociation and transfer efficiency in devices, thus leading to reduced bimolecular recombination. Furthermore, Ti3 C2 T x with appropriate content has little effect on the interpenetrating network morphology and instead provides an additional pathway for charge transport in photoactive layers. Herein, a potential direction for the application of 2D Ti3 C2 T x materials in the field of OSCs is provided. Abstract : 2D Ti3 C2 T x nanosheets are fabricated and incorporated into the active layer of devices as a third component to obtain an enhancement of the photovoltaic device performance. The optimized devices based on PBDB‐T:ITIC@Ti3 C2 T x and PM6:Y6@Ti3 C2 T x reach a power conversion efficiency of 10.72% and 16.25%, respectively.